2018
DOI: 10.3390/ijms19092688
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA Dysregulation in Childhood Hematological Cancer

Abstract: For decades, cancer biology focused largely on the protein-encoding genes that have clear roles in tumor development or progression: cell-cycle control, apoptotic evasion, genome instability, drug resistance, or signaling pathways that stimulate growth, angiogenesis, or metastasis. MicroRNAs (miRNAs), however, represent one of the more abundant classes of cell modulators in multicellular organisms and largely contribute to regulating gene expression. Many of the ~2500 miRNAs discovered to date in humans regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 233 publications
(276 reference statements)
0
28
0
Order By: Relevance
“…Among them, we noticed some reviews focused on miRNAs in childhood ALL have mentioned miR-100, miR-210, and miR-146a in common. 8,9 In our further literation retrieval, miR-100, 10,11 miR-146a, 12,13 as well as miR-210 14,15 were all reported to have remarkable significance in ALL for several times, especially in pediatric ALL. For example, the restoration of miR-100 in ALL cells suppressed cell proliferation and increased dexamethasone-induced cell apoptosis, 16 while miR-146a was reported to be highly expressed in pediatric ALL bone marrow samples.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Among them, we noticed some reviews focused on miRNAs in childhood ALL have mentioned miR-100, miR-210, and miR-146a in common. 8,9 In our further literation retrieval, miR-100, 10,11 miR-146a, 12,13 as well as miR-210 14,15 were all reported to have remarkable significance in ALL for several times, especially in pediatric ALL. For example, the restoration of miR-100 in ALL cells suppressed cell proliferation and increased dexamethasone-induced cell apoptosis, 16 while miR-146a was reported to be highly expressed in pediatric ALL bone marrow samples.…”
Section: Introductionmentioning
confidence: 76%
“…24,25 Through our literature review, we found some influential review focused on miRNAs in childhood ALL have mentioned miR-100, miR-210, and miR-146a in common. 8,9 In the present study, we focused on genetic variants of miR-100, miR-146a, and miR-210, which were all demonstrated to be participate in carcinogenesis of ALL, 13,14,16 and investigated their association with susceptibility of childhood ALL. Among them, rs7395206 have never been reported in other studies while rs543412 and rs2910164 has not been detected in Chinese childhood ALL groups.…”
Section: Discussionmentioning
confidence: 99%
“…These micro markers have proven to be very promising chALL biomarkers and have widespread clinical applications because of their stability and resistance to degradation in not only blood, but also various biological specimens (such as tissue, sputum, stool and formalin-fixed paraffin-embedded (FFPE) specimens), easily measured, and most importantly, their quantities correlates with the presence of the malignancy or with clinically relevant malignancy features (8,14,(95)(96)(97). Recent studies have revealed that extracellular circulating miRNA levels in secreted membrane vesicles (microvesicles and exosomes), blood serum, and other body fluids can be used as biomarkers to diagnose, classify and predict prognosis of chALL (96,(98)(99)(100)(101). miRNA expression dysregulation in cancers is because of different mechanisms, such as deletion or amplification of miRNA related genes, abnormal transcriptional control of miRNAs, epigenetic dysregulation and defects in the biogenesis machinery of miRNA (102).…”
Section: Mirna Levels Alterationmentioning
confidence: 99%
“…Some tumor suppressor miRNAs are miR-181a, miR-326, and miR-200c, which show frequently down-regulation in chALL (97,98). MicroRNA profiling can also be correlated with relevant clinical information, such as disease aggressiveness and metastatic potential, patient response to therapy, time-to-relapse and OS, and other clinical markers in chALL (101). Based on some investigations, not only can miRNAs regulate and sensitize the MDR phenotype, but also can be served as prognostic markers with potential implications in therapeutic interventions as drugs or therapeutic targets in chALL (103).…”
Section: Mirna Levels Alterationmentioning
confidence: 99%
“…13 Many studies have shown that miRNAs may act as oncogenes or tumor suppressors, contributing to the development of malignant cells in both solid and hematological tumors, including AML. 14 It is believed that abnormal expression of some miRNAs may affect the process of development of leukemic cells or alter the response to treatment in cases of AML. Thus, the ability to reverse this abnormal expression may help influence disease outcome.…”
mentioning
confidence: 99%